Regional social contexts and individual fertility decisions : a multilevel analysis of first and second birth in Western Germany - Karsten Hank (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
This paper investigates whether and how regional social contexts influence fertility decisions of women living in western Germany during the 1980s and 1990s. It is argued that regional opportunity structures as well as local patterns of social interaction and culture may translate into parameters that directly affect individual behaviour. Data from the German Socio-Economic Panel (GSOEP) are linked with a set of regional indicators to estimate multilevel discrete-time logit models for the transition to the first and second child. The empirical analysis provides no evidence that fertility differentials observed at the regional level are due to autonomous contextual effects. It is rather suggested that most of the observed regional variation results from differences in the spatial distribution of individual characteristics.
Keywords: 330; multilevel analysis; fertility; Germany; Fruchtbarkeit; Familienökonomik; Region; Soziale Beziehungen; Regionale Disparität; Schätzung; Alte Bundesländer; Deutschland